Hysteresis scaling by defined hysteron pattern in preisach model - Teerawat Monnor (2018)
© 2012 Newswood Limited. All rights reserved. In this work, Preisach model was used to study dynamic hysteresis properties. The patterns of nonlinear relay operators, the hysterons, with sizes of 20?20 hysterons were varied to construct hysteresis loops. The simulation results show that the homogeneous scatter of hysteron results in the symmetric hysteresis loop. On the other hand, the inhomogeneous patterns of the hysteron provide other interesting hysteresis shapes. For instance, with the asymmetric inhomogeneous hysterons, the modeled hysteresis loops are asymmetry, while diagonally symmetric inhomogeneous hysterons yield symmetric hysteresis loops. Then this technique was applied on real hysteresis loops obtained from experiments. The relationship between main characteristic of the hysteresis behavior and hysteron patterns was established. Good agreement between the simulated loops and those from experiments was found indicating the reliability of this Preisach modeling technique in predicting hysteresis behavior for various field perturbations.